The unskilled labor demand across economic sectors in Malaysia: Panel analysis - Muhammad Zakir, Abdullah (2014)
This study is to examine the unskilled labor demand across the major sectors in Malaysia. By using panel data analysis on unskilled labor demand model, the responsiveness how unskilled labor employment on its determinants can be determined in long run. This research employs 13 years of secondary data form 2000 to 2012 across the Malaysian manufacturing, agriculture and services sectors. The finding suggests there is less responsiveness of wage and productivity on unskilled labor demand in these three sectors. The capital cost is very responsive on unskilled labor employment in Agriculture. The imported input cost and foreign labor employment is less sensitive with unskilled labor employment in agriculture. However, there is no evidence the impact of capital cost, imported input cost and foreign labor on unskilled labor employment